PREVALENCE AND RISK FACTORS OF LYNXACARIOSIS IN CATS AT DENPASAR - Angeline Amelinda Palit; Putu Ayu Sisyawati Putriningsih; Ida Bagus Windia Adnyana (Fakultas Kedokteran Hewan Universitas Udayana, 2025)
Animal health conditions have a direct impact on the city's image, influencing local residents' and visitors' perceptions of neighborhood cleanliness, health and safety. The ease with which cats can breed opens up opportunities for the spread of ectoparasitic infestations such as Lynxacarus radovskyi. This study aimed to obtain information and scientific data on the prevalence of lynxacariosis cases and risk factors for its occurrence. A total of 81 cats were used with sample examination methods such as superficial skin scrapping, tape acetate preparation test, and trichogram. The results of this study found that the prevalence of lynxacariosis in Denpasar was 12.3% (10/81) and the risk factor associated with the incidence of lynxacariosis was age (r = 0.024) and it was found that age had an 8 times risk (OR = 8,270) for the spread of lynxacariosis in Denpasar. Lynxacariosis needs to be considered as one of the differential diagnoses in feline skin diseases where the characteristic sign of granules resembling “salt-and-pepper” is not always seen but the scale is often seen, this will help veterinarians provide appropriate and effective treatment for infected cats.